2016
DOI: 10.1007/s10863-016-9664-x
|View full text |Cite
|
Sign up to set email alerts
|

The non-apoptotic action of Bcl-xL: regulating Ca2+ signaling and bioenergetics at the ER-mitochondrion interface

Abstract: Bcl-2 family proteins are known to competitively regulate Ca(2+); however, the specific inter-organelle signaling pathways and related cellular functions are not fully elucidated. In this study, a portion of Bcl-xL was detected at the ER-mitochondrion interface or MAM (mitochondria-associated ER membrane) in association with type 3 inositol 1,4,5-trisphosphate receptors (IP3R3); an association facilitated by the BH4 and transmembrane domains of Bcl-xL. Moreover, increasing Bcl-xL expression enhanced transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“… 99 Moreover, BCL-2 and BCL-X L can localize at the mitochondria-associated ER membranes, with Type III IP3Rs favouring transmission of calcium to the mitochondria, reducing calcium stores ( Figure 5 , panel B inset). 100 , 101 Although many details remain unclear, it has been hypothesized that anti-apoptotic proteins promote the slow leak of calcium from the ER, decreasing the potential for strong signaling to mitochondria and thereby inhibiting apoptosis. 101 BAX/BAK and BH3-only proteins may oppose calcium leakage by binding BCL-2/BCL-X L or IP3R, increasing calcium stores and promoting apoptosis.…”
Section: Changing Dance Partners Within the Cellmentioning
confidence: 99%
“… 99 Moreover, BCL-2 and BCL-X L can localize at the mitochondria-associated ER membranes, with Type III IP3Rs favouring transmission of calcium to the mitochondria, reducing calcium stores ( Figure 5 , panel B inset). 100 , 101 Although many details remain unclear, it has been hypothesized that anti-apoptotic proteins promote the slow leak of calcium from the ER, decreasing the potential for strong signaling to mitochondria and thereby inhibiting apoptosis. 101 BAX/BAK and BH3-only proteins may oppose calcium leakage by binding BCL-2/BCL-X L or IP3R, increasing calcium stores and promoting apoptosis.…”
Section: Changing Dance Partners Within the Cellmentioning
confidence: 99%
“…In a recent study, we have recently shown that breast cancer bioenergetics are also controlled by members of the BCL-2 protein family, a family of proteins originally shown to be primarily involved in apoptosis regulation ( Czabotar et al, 2014 ). However, it is now becoming increasingly evident, that BCL-2 family proteins also regulate mitochondrial fusion and fission dynamics and may regulate mitochondrial respiratory chain activity ( Chen and Pervaiz, 2007 ; Alavian et al, 2011 ; Hardwick and Soane, 2013 ; Gross, 2016 ; Williams et al, 2016 ). BCL2 and BCL(X)L selective inhibitors (Venetoclax and WEHI-539, respectively) were able to decrease mitochondrial bioenergetics and ATP production ( Lucantoni et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this notion, Bcl-x L is predominantly found in the mitochondrial membrane (55), but it is also present in the endoplasmic reticulum and within the cytosol (56). Outside of the mitochondria, Bcl-x L exerts functions distinct to its role in survival, such as controlling Ca 2+ transport, metabolite consumption, and bioenergetics (57). Here, we demonstrated a previously uncharacterized function of Bcl-x L in inhibiting cell metabolism and mitochondrial biogenesis, which suppressed mTOR activation and led to a reduction in cell surface abundance of c.…”
Section: Discussionmentioning
confidence: 76%